2019
DOI: 10.1055/a-0850-9448
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life but not Cognition is Impacted by Radiotherapy in Patients with Non-Functioning Pituitary Adenoma

Abstract: Non-functioning pituitary adenomas (NFPA) are benign neoplasms that are first treated by surgery and secondary radiation therapy in case of residual tumor or regrowth. The consequences of surgery and radiotherapy are still debated. The objective of the work was to assess the impact of surgery, radiotherapy (RT) and pituitary deficiencies on long term health-related quality of life (QoL) and cognitive function among NFPA patients. Forty-six NFPA patients were studied after 9.6±7.5 years follow-up using: i) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…In contrast, Crouzeix et al, in a study based on 46 patients followed for almost 10 years, reported that patients treated with radiotherapy for non functioning pituitary adenoma (NFPA) did not present with cognitive deficits but did show altered quality of life. However, they also suggested that this might be due to a higher rate of pituitary deficiencies rather than to the radiotherapy itself (31). To our knowledge, only one retrospective cross-sectional study has evaluated the cognitive effects of GK in patients treated for a pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Crouzeix et al, in a study based on 46 patients followed for almost 10 years, reported that patients treated with radiotherapy for non functioning pituitary adenoma (NFPA) did not present with cognitive deficits but did show altered quality of life. However, they also suggested that this might be due to a higher rate of pituitary deficiencies rather than to the radiotherapy itself (31). To our knowledge, only one retrospective cross-sectional study has evaluated the cognitive effects of GK in patients treated for a pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…The goal for PA treatment is to eliminate tumor compression, protect nerve function, restore hormone and metabolic order ( 23 ). Numerous studies ( 16 , 24 , 25 ) have reported that PA patients have symptoms such as fatigue, infertility, daytime sleepiness, sleep disturbance, depression and anxiety, etc., which often persist even after PA resection. The complications and high recurrence rate of PA have caused major blows to patients, and patients often cannot adapt properly ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue will appear in patients after surgery and will persist for several months [7]. In some patients, sleepiness and fatigue will last for several years or even longer, which seriously affects the quality of life of patients and is not conducive to their return to the work and life [8,9].…”
Section: Introductionmentioning
confidence: 99%